2019
DOI: 10.1186/s12911-019-0752-9
|View full text |Cite
|
Sign up to set email alerts
|

Rare disease knowledge enrichment through a data-driven approach

Abstract: Background Existing resources to assist the diagnosis of rare diseases are usually curated from the literature that can be limited for clinical use. It often takes substantial effort before the suspicion of a rare disease is even raised to utilize those resources. The primary goal of this study was to apply a data-driven approach to enrich existing rare disease resources by mining phenotype-disease associations from electronic medical record (EMR). Methods We first appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…After a second review of this set of papers, including full text reviews, a selection of 15 candidate best papers was established [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Five reviewers reviewed these pre-selected papers to best four best papers [4][5][6][7]. In direct line with the research presented last year [1], the four best papers published in 2019 demonstrated even further the added-value of ontology-based data integration approaches and that the development of ontology methods is an active area of bioinformatics research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a second review of this set of papers, including full text reviews, a selection of 15 candidate best papers was established [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Five reviewers reviewed these pre-selected papers to best four best papers [4][5][6][7]. In direct line with the research presented last year [1], the four best papers published in 2019 demonstrated even further the added-value of ontology-based data integration approaches and that the development of ontology methods is an active area of bioinformatics research.…”
Section: Resultsmentioning
confidence: 99%
“…Section editors achieved a first selection of 148 papers based on titles and abstracts. After a second review of this set of papers, including full text reviews, a selection of 15 candidate best papers was established 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 . Five reviewers reviewed these pre-selected papers to best four best papers 4 5 6 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study discusses combining existing rare disease knowledge resources and data within the electronic medical record to assist in identifying rare disease phenotypes. 186 In addition, identification of naturally occurring disease models in companion animals that are representative of rare human diseases can result in translation therapies that improve both animal and human lives. For example, osteosarcoma (OSA) is a type of bone cancer that while the most common bone tumor in humans, is very rare with <1000 new cases diagnosed in the United States each year and half of those diagnosed are under the age of 25.…”
Section: Applications Of Veterinary Informaticsmentioning
confidence: 99%
“…Additionally, a DDSS based on phenotypic information extraction using collaborative filtering in combination with natural language processing (NLP) was created. Firstly, it was applied to an EHR database encompassing multiple RDs, afterwards being improved by the addition of literature mining [37,38]. Ada XD is a promising DDSS prototype using the augmented Quick Medical Reference (QMR) Bayesian network with an incorporated probabilistic reasoning engine.…”
Section: Phenotype-driven Diagnosismentioning
confidence: 99%